Sustainment operations during the Aleutian Islands campaign. - Guzman, Paul A. (Fort Leavenworth, KS : US Army Command and General Staff College, 2022)
Global climate change is increasing access to previously closed sea lanes and land masses to exploitation by interested countries. Increasing challenges in the Arctic from countries like the Russian Federation and People's Republic of China threaten stability and access in the Arctic. The US commitment to presenting a credible military deterrence in the Arctic demands an Arctic capable force that can operate in a variety of Arctic conditions, including Arctic islands. The Aleutian Islands Campaign as a case study, can provide examples, lessons, and insights into sustaining modern Arctic operations.